RATIONING ASSEMBLY-MOUNTING WORKS AT THE DEVELOPING ELECTRONIC EQUIPMENT FOR NUCLEAR POWER PLANTS - I. A. Loskutov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives The aim of the study is to simulate assembly and installation work when creating equipment for nuclear power plants based on radio electronicsMethod The study is based on methods of mathematical modeling of technological processes.Result This work is the structuring of knowledge on the assembly and installation of electronic equipment for nuclear power plants. Known methods for the production of printed circuit boards are described. Since the application of solder paste is one of the most responsible technological methods, to minimize the occurrence of defective prints, it is necessary to precisely select the components and make the appropriate chemical composition. For the model of the “Entry-Exit” system, the parameters of the input and disturbing array are shown.Conclusion Taking into account the parametric dependences and the effect of fatigue during sequential operation, an equation is obtained that allows, as a first approximation, to normalize assembly and installation works. Mounted mounting is not taken into account in the equation, as This process is more rational to carry out during the direct assembly of equipment or its components.